1998
DOI: 10.1103/physrevlett.81.1251
|View full text |Cite
|
Sign up to set email alerts
|

Spinodal Dewetting of Thin Polymer Films

Abstract: Dewetting of polystyrene films on a silicon substrate is investigated as a function of film thickness h. We observe the nucleation of holes in the early stage of dewetting for relatively thick films ͑h. 100 Å͒, as observed previously, but the breakup of thinner films occurs through the growth of uniformly distributed surface undulations ("spinodal dewetting"). The average amplitude dh of these undulations increases exponentially up to the film rupture point where dh becomes comparable to h, as predicted by a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
598
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 599 publications
(635 citation statements)
references
References 24 publications
34
598
2
1
Order By: Relevance
“…As can be seen in Figure 2b) and 2c), both the radial profile and the dynamic TEM images capture well the evolution of the dewetting self-assembly process, which is attributed to a spinodal thin-film instability [35][36][37][38] . Spinodal thin-film instabilities are initiated by surface wave perturbations and importantly have correlated time and length scales.…”
mentioning
confidence: 75%
“…As can be seen in Figure 2b) and 2c), both the radial profile and the dynamic TEM images capture well the evolution of the dewetting self-assembly process, which is attributed to a spinodal thin-film instability [35][36][37][38] . Spinodal thin-film instabilities are initiated by surface wave perturbations and importantly have correlated time and length scales.…”
mentioning
confidence: 75%
“…101 It is commonly admitted that nucleation occurs in the early stage of dewetting and spinodal dewetting is promoted for thin films. 101,102 On gold samples, the values of polar components (g + + g À ) were ten times lower than those of the apolar one (g LW ); hence, following Lee's idea, it indicated that gold surface exhibits a strong stabilizing force towards the film. The SEM images showed the beginning of the dewetting process through the heterogeneous nucleation (white spots) stopped before the growth of holes…”
Section: Discussionmentioning
confidence: 99%
“…ting structure have been extensively studied (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Here, we have investigated the dewetting of oleo-liquid film containing octyl p-methoxycinnamate and octylsilyl titanium dioxide particle having average diameter of 35 nm on glass surface.…”
Section: Resultsmentioning
confidence: 99%
“…Wave vector of the fastest growing fluctuation q M , is theoretically in inverse proportion to square root of interfacial tension (4,9). The characteristic length of the fastest growing fluctuation should thus increase as increasing the interfacial tension.…”
Section: Results Andmentioning
confidence: 99%
See 1 more Smart Citation